Effects of bronchial provocation test and bronchial dilation test for the diagnosis of lung diseases. Issue 1 (4th December 2019) - Feng, Mingxia; Yang, Xuemei; He, Yong
Abstract: Aim: Present study was performed to explore the effects of bronchial provocation test (BPT) and bronchial dilation test (BDT) for the diagnosis of lung diseases. Methods: BPT and BDT results were respectively detected by methacholine and albuterol in patients with different lung diseases and non-lung diseases. BPT and BDT indexes including exhaled nitric oxide (ENO), forced expiratory volume of first minute (FEV1), forced vital capacity (FVC), diffusion of carbon monoxide in the lungs (DLCO) and eosinophilia (EOS) were compared by t -test between different groups. Results: Positive and negative BPT indexes were significantly different in lung diseases, similar results of BDT results were also discovered in patients with lung diseases ( p  < .001). Obvious differences of ENO, FEV1/FVC and EOS levels were discovered in different BPT degrees ( p  < .05). FEV1, FVC and FEV1/FVC levels were distinctly higher in I BDT degree than II and III BDT degrees ( p  < .05) in lung diseases. Significant differences of BPT and BDT indexes were discovered between different lung diseases ( p  < .05). Conclusion: BPT and BDT may be employed as the tools for diagnosis of lung diseases. Moreover, the patients with different lung diseases show significantly different BPT and BDT indexes.